Zones of concentrated deformation (flower structures): field observations and modeling data - M. G. Leonov; Yu. A. Morozov; Yu. P. Stefanov; R. A. Bakeev (Геодинамика и тектонофизика)
Our study was focused on narrow linear zones that penetrate to different depths the crust and have complex infrastructure. Rocks in such zones are more intensively tectonically altered in comparison with the background. ‘Flower structures’ and ‘zones of concentrated deformation’ (ZCD) are the terms to describe these zones. The field study results combined with the data of tectonophysical and computational modeling data and supplemented by the literature analysis gave grounds for the following conclusions. In the experiments, as well as in nature, ZCDs show similar and, in some cases, identical morphological and infrastructural features and have similar stages of their evolution. A ZCD is mainly a reflection of the transpression setting. Its formation is accompanied by 3D plastic shear flow of matter and dilatancy of the deformed volume. A ZCD may be associated with the development of the ‘basement – cover’ system. It may also occur due to the intra-cover tectogenesis that does not influence the basement. Locations of ZCDs are spatially regular and predetermine the tectonic divisibility of the crust and lithosphere.